Optimising storage conditions and processing of sheep urine for nitrogen cycle and gaseous emission measurements from urine patches - Alice F. Charteris (Nature Portfolio, 2021)
Abstract In grazing systems, urine patches deposited by livestock are hotspots of nutrient cycling and the most important source of nitrous oxide (N2O) emissions. Studies of the effects of urine deposition, including, for example, the determination of country-specific N2O emission factors, require natural urine for use in experiments and face challenges obtaining urine of the same composition, but of differing concentrations. Yet, few studies have explored the importance of storage conditions and processing of ruminant urine for use in subsequent gaseous emission experiments. We conducted three experiments with sheep urine to determine optimal storage conditions and whether partial freeze-drying could be used to concentrate the urine, while maintaining the constituent profile and the subsequent urine-derived gaseous emission response once applied to soil. We concluded that filtering of urine prior to storage, and storage at − 20 °C best maintains the nitrogen-containing constituent profile of sheep urine samples. In addition, based on the 14 urine chemical components determined in this study, partial lyophilisation of sheep urine to a concentrate represents a suitable approach to maintain the constituent profile at a higher overall concentration and does not alter sheep urine-derived soil gaseous emissions.